2020
DOI: 10.3390/genes11060589
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Epidemiology of Cystic Fibrosis: Incidence, Survival and Impact of the CFTR Gene Discovery

Abstract: Significant advances in the management of cystic fibrosis (CF) in recent decades have dramatically changed the epidemiology and prognosis of this serious disease, which is no longer an exclusively pediatric disease. This paper aims to review the changes in the incidence and survival of CF and to assess the impact of the discovery of the responsible gene (the CFTR gene) on these changes. The incidence of CF appears to be decreasing in most countries and patient survival, which can be monitored by various indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
155
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(164 citation statements)
references
References 82 publications
3
155
0
6
Order By: Relevance
“…A study done by Courteny et al indicated an average case fatality rate of 24.6 in adults (11). Lower BMI and lower PFT results are in general associated with higher mortality reported from various studies from different parts of the world (12)(13)(14), as seen in our study.…”
Section: Discussionsupporting
confidence: 80%
“…A study done by Courteny et al indicated an average case fatality rate of 24.6 in adults (11). Lower BMI and lower PFT results are in general associated with higher mortality reported from various studies from different parts of the world (12)(13)(14), as seen in our study.…”
Section: Discussionsupporting
confidence: 80%
“…Cystic fibrosis (CF) is the most common life-limiting, autosomal, recessively inherited disease in Caucasian populations, with the primary cause of death being respiratory failure resulting from chronic pulmonary infection (22). CF patients have reduced lung clearance capacity, leading to the development of lifelong chronic infections caused by opportunistic bacterial pathogens, such as Pseudomonas aeruginosa.…”
mentioning
confidence: 99%
“…According to the analysis by Keogh et al [ 32 ], it is expected that more than half of children with CF born today will live to at least the fifth decade of life. Access to modern treatment, such as CFTR modulator therapies, contributed to the extension and improvement of patients’ life quality [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is the result of the development within many areas of CF care. Many factors are responsible for these major advances in treatment such as standardisation with high-quality healthcare of patients in specialised centres by multidisciplinary teams, better control of pulmonary infection with the development of new inhaled therapies, better control of Pseudomonas aeruginosa colonisation, availability of modern treatment including the cystic fibrosis transmembrane conductance regulator (CFTR) modulators, aggressive nutritional supplementation with pancreatic enzymes, early diagnosis through newborn screening, and lung transplantation [ 14 , 15 , 16 ]. In spite of this development, CF remains a progressive lethal disease.…”
Section: Introductionmentioning
confidence: 99%